Vermicompost bioenriched whit Trichoderma spp. - Michelon, Cleudson José; Rosa Neto, Lethícia; Oruoski, Pâmela; Oliveira, Marília Boff de; Vieira, Caroline Castilhos; Junges, Emanuele (Revista de Ciências Agroveterinárias, 2018)
The intensification of agropastoral activity leads to a high production of waste. The composting of these residues produces an agricultural input with high potential in the production of vegetables and with the possibility of association with organisms of biological control, allowing the production of an ecologically correct substrate, rich in nutrients and protector of the health of the plants. In this sense, the objective of this work was to evaluate the survival of the fungus Trichoderma spp. During the vermicompost process, as the physical / chemical development caused not substrate and the growth and development of lettuce plants grown in the different treatments used. Basal substrates were obtained from the creation of three different animals: sheep, Horses and rabbits, whether or not containing added Trichoderma spp. In all treatments, worms of Eisenia foetida were added. Evaluations of fungus survival, physical and chemical analyzes of the substrate produced and evaluation without growth and development of lettuce plants were carried out. The treatments were arranged in a 3x2 factorial scheme and the experimental design was completely randomized, with 4 replicates. Data were analyzed using Sisvar® software, and as means averages compared by Scott Knott’s test at 5% error probability. Trichoderma spp. It survives the vermicompost process by improving the development of lettuce plants when associated with farms residue. The use of Trichoderma spp. It reduced the calcium values of all substrates, raised a dry density of the base substrate of rabbit residues, and reduced the base substrate of farmyard residues. The substrate that provided the best growth and development of lettuce plants was the residues of rearing of horses, being favored by the presence of Trichoderma spp. in the second year.